1993
DOI: 10.1016/0014-5793(93)81271-z
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase

Abstract: Core histones can be modified by reversible, posttranslational acetylation of specific lysine residues within the N-terminal protein domains. The dynamic equilibrium of acetylation is maintained by two enzyme activities, histone acetyltransferase and histone deacetylase. Recent data on histone deacetylases and on anionic motifs in chromatin-or DNA-binding regulatory proteins (e.g. transcription factors, nuclear proto-oncogenes) are summarized and united into a hypothesis which attributes a key function to hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…The intact and fragmented DNAs in the Recently, it has been shown that acetylation, one of the postcells were assayed as described previously [12]. DNA fragmentation translational modifications of core histones [3], induces unwas expressed as a percentage of total DNA (intact plus fragmented folding of the chromatin fiber [4,5]. DNA).…”
Section: Dna Fragmentationmentioning
confidence: 99%
“…The intact and fragmented DNAs in the Recently, it has been shown that acetylation, one of the postcells were assayed as described previously [12]. DNA fragmentation translational modifications of core histones [3], induces unwas expressed as a percentage of total DNA (intact plus fragmented folding of the chromatin fiber [4,5]. DNA).…”
Section: Dna Fragmentationmentioning
confidence: 99%
“…In most experimental systems investigated so far histone acetyltransferases and deacetylases exist as multiple enzyme forms; in pea, three histone deacetylases exist [26]. In maize we could distinguish four histone deacetylases [16,17,20,22,29]. The four histone deacetylases of maize are distinct with respect to their biochemical and kinetic properties [29], to modification by phosphorylation [20], pattern of enzyme activity during the cell cycle and differentiation [16][17][18], substrate specificity [16,20,29] and subnuclear localization [22].…”
Section: Discussionmentioning
confidence: 93%
“…The amino terminal histone tails can be acetylated at certain lysine residues, resulting in a decrease of the net positive charge on one hand, and in an alteration of their specific binding properties for regulatory proteins on the other hand. A change in the specific acetylation pattern of core histones has therefore been correlated with changes in the transcriptional activity of genes [11,[42][43][44]. Core histone N-termini and their acetylation also play a complex, but still poorly understood role in DNA replication [14,15,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations